Pengaruh Laba Akuntansi Dan Laba Tunai Terhadap Dividen Kas - RISA RUKMANA (Tangible Journal, 2019)
This study aims to determine the effect of accounting profit and cash profit on cash dividends in manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the year 2016-2018. Using the purposive sampling method. The study was analyzed using multiple linear regression with SPSS software version 21. Based on the results of the study it can be concluded that accounting profit and cash profit simultaneously have a significant effect on cash dividends and partially accounting profits have a significant effect on cash dividends on manufacturing companies listed on the Indonesian stock exchange, but there is one variable, namely cash income which has no significant effect on cash dividends on manufacturing companies listed on the Indonesian stock exchange.